Assessment of optic disc and ganglion cell layer in diabetes mellitus type 2. Issue 29 (July 2017) - Pekel, Evre; Tufaner, Gökhan; Kaya, Hüseyin; Kaşıkçı, Alper; Deda, Gökhan; Pekel, Gökhan
Abstract : Abstract: The purpose of this study was to compare the optic disc parameters, retinal nerve fiber (RNFL), and macular ganglion cell layers between patients with diabetes mellitus (DM) type 2 and healthy controls. In this cross-sectional study, 69 eyes of 69 diabetic patients without diabetic retinopathy and 47 eyes of 47 healthy controls were included. Optic disc parameters (i.e., rim area, disc area, cup to disc ratio, cup volume), RNFL, and macular ganglion cell-inner plexiform layers (GCL + IPL) thickness were measured by means of spectral domain optical coherence tomography. There were not statistically significant differences between the diabetic patients and healthy controls in terms of RNFL thickness ( P = .32), rim area ( P = .20), disc area ( P = .16), cup volume ( P = .12), and average macular GCL + IPL thickness ( P = .11). Nevertheless, binocular RNFL thickness symmetry percentage ( P =.03), average cup to disc ratio ( P = .02), and superior-nasal macular GCL + IPL thickness ( P = .04) were statistically significantly different in the diabetic and control groups. Diabetic patients without retinopathy have more binocular RNFL thickness asymmetry, higher cup to disc ratio, and thinner sectoral macular GCL + IPL when compared to healthy controls. Our results may support the statement that DM causes inner retinal neurodegenerative changes.